1996
DOI: 10.1029/95jd01704
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the mesosphere and lower thermosphere as seen by MF radars and by the high‐resolution Doppler imager/UARS

Abstract: This paper presents comparisons between wind measurements in the mesosphere and lower thermosphere by medium‐frequency (MF) radars and by the high‐resolution Doppler imager onboard the Upper Atmosphere Research Satellite (UARS). Because of distinctive observational patterns, time and space averaging, and data processing algorithms, satellites and radars observe the atmosphere from their own perspectives. Because thermal tides are an important part of dynamics in these regions of the atmosphere, tidal determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 21 publications
(11 reference statements)
1
56
0
Order By: Relevance
“…Burrage et al, 1996;Khattatov et al, 1996). It is not obvious that these di erences re¯ect a poor wind measurement per se, but if the radar is not measuring the wind accurately, it will obviously lead to errors in the calculations we present.…”
Section: Numerical Techniques and Datamentioning
confidence: 94%
“…Burrage et al, 1996;Khattatov et al, 1996). It is not obvious that these di erences re¯ect a poor wind measurement per se, but if the radar is not measuring the wind accurately, it will obviously lead to errors in the calculations we present.…”
Section: Numerical Techniques and Datamentioning
confidence: 94%
“…In validation studies, the variability of the observed values has often been expressed by the mean-square di erence of the anomalies (e.g., Khattatov et al, 1996):…”
Section: Estimation Of the Precisionmentioning
confidence: 99%
“…In this comparison it will be obvious that there are some signi®cant di erences between the ground-based and satellite-based estimates of mean, tidal, and planetary wave parameters. Although not fully resolved, this issue has been addressed at a number of workshops (Geller, 1994), and in recent papers by Khattatov et al, (1996) and Burrage et al (1996). Therefore, in cases where the ground-and satellite-based measurements disagree we will provide our best estimate of the model performance based upon current knowledge of possible instrumental biases and refer the reader to the aforementioned references for additional information.…”
Section: Introductionmentioning
confidence: 99%